PEMBERDAYAAN KELOMPOK TANI SAWAH PAYO KABUPATEN TANAH DATAR MELALUI TEKNIK PEMANGKASAN TANAMAN KAKAO (Jurnal Hilirisasi IPTEKS, 2020)
The problem that is often faced by the Payo Rice Field Farmers group in producing cocoa beans is the cocoa tree that has aged and damaged due to disease pests. To overcome this problem, it is necessary to intensify efforts, for example by fertilizing, maintaining soil and plants as well as pruning and rehabilitation by replanting new cocoa trees. The purpose of this farmer group empowerment activity is to provide knowledge about the techniques and the process of pruning cocoa cultivation plants that are good and right in accordance with the cultivation procedures that are supposed to be able to increase the productivity results of these plants. The method used in this activity is the method of direct and indirect approach. The direct approach method is by conducting interviews with the Gunung Rajo community and by conducting direct socialization and demonstration in the field. The indirect method used is observation. Observation is an observation made to find out the habit. The results obtained from this empowerment activity are the Payo Rice Field farmer groups can carry out routine pruning activities on the cocoa plants they cultivate and can maintain their cocoa plants so that they can increase their yield.